A Review on Mpox: Diagnosis, Prevention and Treatments - Sharma, Himanshu; Tyagi, Siddhant Jai; Varshney, Prakhar; Pathak, Neha; Pathak, Rashmi (Coronaviruses, 2025)
Mpox is a zoonotic disease caused by the orthopox virus, and its signs and symptoms are similar to those of smallpox in humans. As public health organizations try to end the present epidemic, healthcare professionals across the globe place a high premium on their education on the many clinical symptoms and possible treatments for this virus. For those who are affected, there is currently no cure. However, due to the smallpox outbreak, specialists are now looking at vaccinia immune globulin (IVG), tecovirimat, and cidofovir as potential remedies for Mpox. In severe cases, tecovirimat and supportive care may be used with drugs to aid with symptom alleviation. The World Health Organization (WHO) reports that the EMA acknowledged tecovirimat as a secure and reliable therapy for Mpox in 2023. The effectiveness of these therapies is fiercely contested since there are clear guidelines for decreasing these symptoms. Moreover, by examining elements such as the quantity of confirmed, probable, and possible cases, the median age at presentation, the fatality rate, and the geographic distribution of the disease, we hoped to understand the epidemiology of Mpox better as it was changing throughout this study. In light of recent widespread outbreaks, this page provides an updated analysis of Mpox and the medical remedies that are now accessible.
Keywords: surveillance